Photopolymerization kinetics of 2-phenylethyl (meth) acrylates studied by photo DSC - Ghorpade, Ravindra V.; Bhosle, Sonali Madhavrao; Ponrathnam, S.; Rajan, C. R.; Chavan, Nayaku; Harikrishna, Reghunathan (Journal of Polymer Research, 2012)
The present work deals with the photopolymerization of 2-phenylethyl (meth)acrylates and estimation of their kinetic parameters. Formulations were made by independently homogenizing the monomers with photoinitiators of two different classes. Two different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using differential photocalorimetry (DPC) or photo DSC under polychromatic radiation. The heat flow against time was recorded for all formulations under isothermal conditions and the rates of polymerization as well as the percentage conversions were estimated. It was observed that due to a longer timescale for reaction diffusion, the methacrylate formulations showed a higher conversion than acrylate formulations. Other parameters such as induction time, maximum rate and conversion attained as well as the time to attain peak maximum were noted. The photopolymerization and kinetic estimations of the formulations including evaluation of kinetic models are discussed.
Keywords: Bimolecular termination model; Photo DSC; Photopolymerization; Variable autocatalytic model